A window on cyclitols: Characterization and analytics of inositols. (June 2017) - Al-Suod, Hossam; Ligor, Magdalena; Rațiu, Ileana-Andreea; Rafińska, Katarzyna; Górecki, Ryszard; Buszewski, Bogusław
Graphical abstract: Highlights: Cyclitols play an important role in cell functioning. d -pinitol is efficient in blood glucose lowering and act as antioxidant agent. Solvent extraction followed by GC or LC–common procedures in analysis of cyclitols. Ultrasound-assisted and supercritical fluid extraction allowed cyclitols isolation. Abstract: Cyclitols are cycloalkanes with one hydroxyl group on each of three or more ring atoms, also called cycloalkane polyols or sugar alcohol which attract attention since they have numerous pharmaceutical properties and are widespread in the plants. Inositols are important cyclitols, which constitute a group of naturally occurring polyhydric alcohols and some isomers of this group can be commonly found in most plants, provided adequate methods of detection are employed. This review presents plant containing cyclitols, with emphasis put on their pharmaceutical properties. The text focuses on sample preparation, extraction and purification and on analysis of cyclitols in plants. In addition, it addresses the application of different methodologies utilized in the analysis of cyclitol compounds in plant.